Multi-core optical fiber

By controlling the refractive index difference and stress distribution between the core and cladding of multi-core optical fibers, the problem of insufficient transmission loss in existing technologies has been solved, and a significant reduction in transmission loss has been achieved.

CN120858306APending Publication Date: 2025-10-28SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480017671.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-15
Filing Date
2024-02-13
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In existing technologies, it is difficult to sufficiently reduce the transmission loss of multi-core optical fibers by relying solely on the compressive stress between adjacent fiber cores.

Method used

Multi-core optical fibers made of silica-based glass are used. By controlling the refractive index difference between the core and cladding and the distribution of residual stress, the stress difference between the cores is ensured to be below 30 MPa, and the proportion of the compressive stress region in the entire region is controlled to be below 40%, so as to reduce transmission loss.

Benefits of technology

The transmission loss of multi-core optical fibers has been significantly reduced, especially when the stress difference is below 10 MPa and the proportion of the compressive stress region is below 25%, the transmission loss is further reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120858306A_ABST
    Figure CN120858306A_ABST
Patent Text Reader

Abstract

The multi-core optical fiber (1) is composed of silica-based glass. A multi-core optical fiber (1) is provided with: a plurality of cores (2) containing one or more elements from among an alkali metal element group including an alkali metal element and an alkaline earth metal element; and a cladding (3) covering the core and having a refractive index lower than the refractive index of the core. In a cross section orthogonal to the optical fiber axis, the difference between the maximum value of residual stress on a line segment (L) connecting the centers of adjacent ones of the plurality of cores and the average value of residual stress of the plurality of cores (2) is 30 MPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to multi-core optical fibers. This application claims priority based on Japanese Application No. 2023-040847, filed on March 15, 2023, and invokes all the contents described in that Japanese application. Background Technology

[0002] Generally, if the fiber core, made of silica-based glass, contains alkali metals or alkaline earth metals, the viscosity of the fiber core decreases and the glass rearrangement is promoted during fiber drawing to manufacture the optical fiber. Therefore, the transmission loss caused by Rayleigh scattering in the optical fiber is reduced. Hereinafter, both alkali metals and alkaline earth metals will be referred to as the "alkali metal element group." Patent documents 1 to 3 describe multi-core optical fibers (hereinafter, MCFs) with a core made of silica-based glass containing the alkali metal element group.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-40878

[0006] Patent Document 2: Japanese Patent Application Publication No. 2017-75061

[0007] Patent Document 3: Japanese Patent Application Publication No. 2017-161705

[0008] Non-patent literature

[0009] Non-patent literature 1: M. Koshiba, K. Saitoh, and Y. Kokubun, “Heterogeneous multi-core fibers: proposal and design principle,” IEICE Electron. Express., vol. 6, no. 2, pp. 98-103, Jan. 2009. Summary of the Invention

[0010] One aspect of this disclosure relates to an MCF (Metallic Fluorescent Cell) made of silica-based glass, comprising: multiple fiber cores containing one or more elements from the alkali metal group, including alkali metal elements and alkaline earth metal elements; and a cladding that encloses the fiber cores and has a refractive index lower than that of the fiber cores. In a cross-section orthogonal to the fiber axis, the difference between the maximum value of the residual stress on the line segment connecting the centers of adjacent fiber cores and the average value of the residual stress of the multiple fiber cores is less than 30 MPa. In this specification, when the above-mentioned maximum value (i.e., the maximum stress of the inter-core line segment) is denoted as σmax and the above-mentioned average value (i.e., the average stress of the multiple fiber cores) is denoted as σc, the above-mentioned difference (i.e., stress difference) does not refer to |σmax-σc|, but rather to σmax-σc. Attached Figure Description

[0011] Figure 1 This is a diagram showing the cross-section and refractive index distribution of the MCF orthogonal to the fiber axis according to the embodiment.

[0012] Figure 2 This is a flowchart illustrating the manufacturing method of the MCF involved in the embodiment.

[0013] Figure 3 It is a table that summarizes the specifications of each of the manufactured and evaluated MCFs.

[0014] Figure 4 It is a graph showing the relationship between stress difference and transmission loss of the first fiber core.

[0015] Figure 5 It is a table that summarizes the specifications of each of the manufactured and evaluated MCFs.

[0016] Figure 6 It is a graph showing the relationship between the proportion of the optical fiber cross-sectional area under compressive stress and the transmission loss.

[0017] Figure 7 This is a cross-sectional view showing an example of stress distribution in an MCF. Detailed Implementation

[0018] [The technical problem this disclosure aims to solve]

[0019] Patent document 3 describes a reduction in transmission loss due to compressive stress between adjacent fiber cores. However, compressive stress only between adjacent fiber cores sometimes does not sufficiently reduce transmission loss.

[0020] This disclosure provides an MCF with significantly reduced transmission loss.

[0021] [The Effects of This Disclosure]

[0022] According to this disclosure, an MCF with sufficiently reduced transmission loss can be provided.

[0023] [Description of embodiments of this disclosure]

[0024] First, we will describe the implementation aspects of this disclosure.

[0025] (1) The MCF involved in the first aspect of this disclosure is an MCF made of silica-based glass, comprising: a plurality of fiber cores containing one or more elements from the alkali metal element group, the alkali metal element group including alkali metal elements and alkaline earth metal elements; and a cladding that encloses the fiber cores and has a refractive index lower than that of the fiber cores, wherein in a cross section orthogonal to the fiber axis, the difference between the maximum value of the residual stress on the line segment connecting the centers of adjacent fiber cores and the average value of the residual stress of the plurality of fiber cores is less than 30 MPa.

[0026] In the aforementioned MCF, transmission loss is significantly reduced.

[0027] (2) In (1) above, the difference can also be greater than -10MPa and less than 10MPa. In this case, the transmission loss is further reduced.

[0028] (3) The MCF involved in the second aspect of this disclosure is an MCF made of silica-based glass, comprising: a plurality of fiber cores containing one or more elements from the alkali metal element group, the alkali metal element group including alkali metal elements and alkaline earth metal elements; and a cladding that encloses the fiber cores and has a refractive index lower than that of the fiber cores, wherein in a cross section orthogonal to the fiber axis, the area of ​​the region of compressive stress is less than 40% of the area of ​​the entire region.

[0029] In the aforementioned MCF, transmission loss is significantly reduced.

[0030] (4) In (3) above, the area of ​​the region experiencing compressive stress may be less than 30% of the total area. In this case, the transmission loss is further reduced.

[0031] (5) In (3) or (4) above, the area of ​​the region experiencing compressive stress may be less than 10% of the total area. In this case, transmission loss is further reliably reduced.

[0032] (6) In any of (1) to (5) above, the multiple fiber cores may each contain one or more elements selected from sodium, potassium, rubidium, cesium, and calcium as an alkali metal element group. In this case, the viscosity of the fiber core and its vicinity is reduced, and the glass rearrangement is promoted, thus reducing the transmission loss of the optical fiber caused by Rayleigh scattering.

[0033] [Details of the embodiments of this disclosure]

[0034] The following description, with reference to the accompanying drawings, illustrates specific examples of the MCF of this disclosure. It should be noted that this disclosure is not limited to these examples, but rather, as illustrated by the claims, is intended to include all modifications within the meaning and scope of the claims. In the description of the drawings, the same reference numerals are used to denote the same elements, and repeated descriptions are omitted.

[0035] Figure 1 This is a diagram showing the cross-section and refractive index distribution of the MCF orthogonal to the fiber axis according to the embodiment. For example... Figure 1 As shown, the MCF1 involved in the embodiment includes multiple fiber cores 2, a first cladding layer 3, and a second cladding layer 4. The MCF1 is made of silica-based glass. Silica-based glass is glass with silica as its main component and containing more than 97% silica.

[0036] Multiple fiber cores 2 have the same circular shape in a cross-section (hereinafter, simply referred to as the cross-section) orthogonal to the fiber axis. The fiber cores 2 extend along the fiber axis. The diameter (core diameter) of the fiber core 2 is, for example, 8 μm or more and 15 μm or less. In this embodiment, the MCF1 is a dual-core fiber, and the number of fiber cores 2 is two, but not limited to this. In the cross-section, the two fiber cores 2 are arranged opposite each other across the central axis of the MCF1. In the cross-section, the two fiber cores 2 are arranged at equal distances from the center of the fiber. In the cross-section, the length of the line segment L connecting the centers of two adjacent fiber cores 2 is, for example, 20 μm or more and 50 μm or less. The length of the line segment L is the center-to-center spacing of the fiber cores 2. The line segment L has a portion located on the two adjacent fiber cores 2 and a portion located on the first cladding 3.

[0037] Multiple fiber cores 2 have the same refractive index. Multiple fiber cores 2 may also have different refractive indices. The average cutoff wavelength of the multiple fiber cores 2 is, for example, above 1300 nm and below 1530 nm. The average effective cross-sectional area of ​​the multiple fiber cores 2 at a wavelength of 1550 nm is, for example, 75 μm. 2 Above and 160μm 2 the following.

[0038] Each of the plurality of fiber cores 2 contains one or more elements from the alkali metal element group, which includes alkali metal elements and alkaline earth metal elements. Each of the plurality of fiber cores 2 contains at least one element selected from sodium, potassium, rubidium, cesium, and calcium as part of the alkali metal element group. In each of the plurality of fiber cores 2, it is sufficient that at least a portion of the fiber core 2 contains an alkali metal element group. The average concentration of the alkali metal element group in the plurality of fiber cores 2 is, for example, 5 ppm or more and 100 ppm or less. Each of the plurality of fiber cores 2 contains, for example, halogens such as chlorine and fluorine.

[0039] The method for determining the concentration of the elements contained in fiber core 2 is as follows. The end face of MCF1, perpendicular to the fiber axis, is ground. Along a straight line passing through the center of fiber core 2, the concentration C(x) of the element being measured at radial position x is determined using an electron probe microanalyzer (EPMA). Radial position x is 0 at the center of fiber core 2. The conditions for the EPMA measurement are, for example, an accelerating voltage of 20 kV, a probe beam diameter of 1 μm or less, and a measurement interval of 100 nm or less. If the radius of fiber core 2 is denoted as ra, the average concentration of the element being measured in the entire fiber core 2 is expressed by the following formula. It should be noted that when fiber core 2 contains two or more elements from the alkali metal group, the sum of the average concentrations obtained for each element is taken as the average concentration of the alkali metal group.

[0040] [Mathematical formula 1]

[0041]

[0042] The first cladding 3 and the second cladding 4 are common claddings that enclose the plurality of fiber cores 2. The first cladding 3 covers the outer peripheral surface of the plurality of fiber cores 2. In cross-section, the first cladding 3 has a circular shape. The diameter of the first cladding 3 is, for example, 50 μm or more and 90 μm or less. The second cladding 4 covers the outer peripheral surface of the first cladding 3. In cross-section, the second cladding 4 has a circular shape. The diameter of the second cladding 4 is, for example, 124 μm or more and 126 μm or less.

[0043] The first cladding layer 3 and the second cladding layer 4 have refractive indices lower than those of the core 2. The refractive index of the second cladding layer 4 is higher than that of the first cladding layer 3. The relative refractive index difference of the second cladding layer 4, based on the refractive index of the first cladding layer 3, is 0.05% or more and 0.25% or less. The relative refractive index difference of the core 2, based on the refractive index of the first cladding layer 3, is 0.25% or more and 0.50% or less. Figure 1 The refractive index distribution is shown with the vertical axis set as the relative refractive index difference Δ relative to the refractive index of the first cladding 3, and the horizontal axis set as the radial position r. The radial position r is 0 at the center of the fiber. MCF1 is a common-recessed type MCF. The first cladding 3 functions as a common-recessed layer.

[0044] Residual stress is applied to MCF1. The average residual stress of the multiple fiber cores 2 is, for example, above -100 MPa and below -20 MPa. Here, stress is represented by a positive value in the case of tensile stress and by a negative value in the case of compressive stress. That is, the residual stress of the multiple fiber cores 2 is compressive stress.

[0045] In a cross-section orthogonal to the fiber axis, the difference between the maximum residual stress on segment L and the average residual stress of the multiple fiber cores 2 (hereinafter, stress difference) is 30 MPa or less. That is, there is no portion of segment L with residual stress exceeding 30 MPa of the average residual stress of the multiple fiber cores 2. Therefore, transmission loss is sufficiently reduced. The stress difference can be, for example, 20 MPa or less, 10 MPa or less, or even -10 MPa or more. In particular, the stress difference can also be -10 MPa or more and 10 MPa or less.

[0046] In the cross-section, the area of ​​the region experiencing compressive stress is less than 40% of the total area of ​​MCF1. Alternatively, the area of ​​the region experiencing compressive stress in the cross-section can be less than 30% or more than 10% of the total area of ​​MCF1. Specifically, the area of ​​the region experiencing compressive stress can also be more than 15% and less than 25% of the total area of ​​MCF1. The residual stress of MCF1 is measured, for example, using an optical system of a microscope and interferometer.

[0047] Figure 2 This is a flowchart illustrating a method for manufacturing the MCF according to an embodiment. Figure 2 As shown, an example of a specific condition is also described in the following explanation. For example... Figure 2 As shown, MCF1 is manufactured by sequentially going through the following steps: preparation process (step S1), addition process (step S2), diameter reduction process (step S3), etching process (step S4), solidification process (step S5), extension grinding process (step S6), sleeve collapse process (step S7), OVD process (step S8) and wire drawing process (step S9).

[0048] In the preparation process (step S1), a glass tube of silica-based glass, into which dopants such as alkali metal elements are diffused, is prepared. The outer diameter of this glass tube is 30 mm or more and 40 mm or less, and the inner diameter is 15 mm or more and 25 mm or less. The silica-based glass cylinder that forms the basis of this glass tube contains chlorine and fluorine. The concentration of chlorine and fluorine contained in this cylinder is the same as the concentration of chlorine and fluorine contained in the core 2 of MCF1. The concentration of other dopants and impurities contained in this cylinder is 10 ppm or less. The concentration referred to here is the average concentration of the entire cylinder. The concentration of elements contained in the cylinder is determined by EPMA, for example, in the same way as the concentration of elements contained in the core 2. The measurement conditions may also differ from those for the core 2. It is acceptable to calculate the concentration using calibration curves under the respective conditions.

[0049] In the addition process (step S2), a dopant of an alkali metal element group is added to the inner surface of the prepared glass tube. Here, the addition of potassium is described. Potassium bromide (KBr) of 6g to 50g is used as raw material. The raw material is heated to a temperature of 750°C to 850°C using an external heat source to generate raw material vapor. While introducing the raw material vapor and a carrier gas containing oxygen at a flow rate of 1SLM (equivalent to 1 liter / min under standard conditions) into the interior of the glass tube, the glass tube is heated from the outside using an oxyhydrogen burner to raise the outer surface of the glass tube to a temperature of 1400°C to 2000°C. At this time, the burner is rotated at a speed of 30mm / min to 60mm / min for a total of 5 to 20 revolutions to diffuse potassium into the inner surface of the glass tube.

[0050] In the diameter reduction process (step S3), the glass tube containing potassium is reduced in diameter. During this process, oxygen is introduced into the glass tube at a rate of 0.5 SLM to 1.0 SLM, while the glass tube is heated using an external heat source to raise the outer surface temperature to 1400°C to 2300°C. The external heat source is then rotated horizontally for a total of 5 to 15 rotations to reduce the glass tube's diameter to an inner diameter of 3 mm to 8 mm.

[0051] In the etching process (step S4), the inner surface of the glass tube is etched. At this time, a mixed gas of SF6 (0.2 SLM or more and 1.0 SLM or less) and chlorine (0.5 SLM or more and 1.0 SLM or less) is introduced into the interior of the glass tube, and the glass tube is heated using an external heat source to perform vapor-phase etching. In this way, the inner surface of the glass tube, which contains a high concentration of impurities added along with the target dopant, can be etched away, and these impurities can be removed.

[0052] In the solidification process (step S5), the glass tube is solidified. In this process, a single or mixed gas of oxygen (0.1 SLM or more and 0.5 SLM or less) and he (0.5 SLM or more and 1.0 SLM or less) is introduced into the interior of the glass tube. While reducing the absolute pressure inside the glass tube to below 97 kPa, the surface temperature is maintained at 2000°C or more and 2300°C, thereby solidifying the glass tube. This solidification process yields a glass rod (outer diameter 20 mm or more and 30 mm or less) that forms the core. Alternatively, a core layer without alkali metal elements can be applied to the outer side of the glass rod using known methods such as OVD (Outside Vapor Deposition) or collapse deposition.

[0053] In the stretching and grinding process (step S6), a glass rod that becomes the core is stretched to a diameter of 15 mm or more and 25 mm or less, and then the outer periphery of the glass rod is ground to a diameter of 15 mm or more and 25 mm or less, thereby obtaining the core. It is assumed that the diameter immediately after stretching is larger than the diameter after grinding. The preparation process up to the stretching and grinding process is performed the same number of times as the number of fiber cores 2 of MCF1, resulting in multiple cores. The core is the portion of the fiber core 2 that becomes MCF1.

[0054] In the sleeve collapse process (step S7), a first cladding portion is provided on the outside of multiple cores. The first cladding portion is the part that becomes the first cladding 3 of MCF1. Multiple cores are inserted into the interior of a fluorinated silica-based glass tube, and sleeve collapse is performed. According to this sleeve collapse method, the multiple cores and the fluorinated silica-based glass tube are integrated by heating with an external heat source. As a result, a first cladding portion is added around the multiple cores. The maximum relative refractive index difference between the cores and the first cladding portion is about 0.30% to 0.45%. As a result of the synthesis performed by this sleeve collapse method, the water content of the cores and the first cladding portion nearby can be sufficiently reduced. The structure of MCF1 can be determined based on the insertion position and number of cores in this process.

[0055] In the OVD process (step S8), after the rod, which is integrally formed from multiple cores and a first cladding portion, is extended to a specified diameter, a second cladding portion containing fluorine is synthesized on the outside of the rod using the OVD method. This produces the optical fiber mother material. The second cladding portion is the part that becomes the second cladding 4 of MCF1.

[0056] In the fiber drawing process (step S9), MCF1 is manufactured by drawing the optical fiber mother material. The drawing speed is 600 m / min or more and 2300 m / min or less. The drawing tension is 0.1 N or more and 1.0 N or less.

[0057] Figure 3 It is a table that summarizes the specifications of each of the manufactured and evaluated MCFs. Figure 3 The MCFs in this context are all dual-core optical fibers with two cores. One of the two cores is designated as the first core, and the other as the second core. Figure 3 For each of the MCFs in samples A1 to A10, the average potassium (K) concentration [ppm] of the two cores, the average core diameter [μm] of the two cores, the average cutoff wavelength (λcc) of the two cores [nm], and the average effective cross-sectional area (Aeff) of the two cores at a wavelength of 1550 nm [μm] are shown. 2The average stress of the two fiber cores [MPa], the maximum stress of the inter-core segment [MPa], the stress difference [MPa], and the transmission loss [dB / km] of the first and second fiber cores at a wavelength of 1550nm.

[0058] Here, the average stress of the two fiber cores is the average of the residual stresses of the two fiber cores. The maximum stress of the intercore segment is the maximum residual stress on the segment connecting the centers of the two fiber cores. The stress difference is the difference between the average stress of the fiber cores and the maximum stress of the intercore segment. The parameters of the second fiber core are values ​​within ±5% of the parameters of the first fiber core. The average stress of the fiber cores and the maximum stress of the intercore segment are varied by controlling the tension during drawing (drawing tension), the linear speed (drawing speed), and the slow cooling after exiting the furnace. The residual stress of the MCF is not a calculated value, but a measured value determined using an optical system of a microscope and interferometer.

[0059] Figure 4 This is a graph showing the relationship between stress difference and transmission loss of the first fiber core. Since the transmission losses of the first and second fiber cores exhibit roughly the same trend, the first fiber core is shown here as a representative value. Figure 4 As shown, the transmission loss of the first fiber core at a wavelength of 1550 nm decreases to below 0.156 dB / km within a stress difference range of less than 30 MPa, indicating a lower transmission loss. The transmission loss of the first fiber core at a wavelength of 1550 nm further decreases to below 0.154 dB / km within a stress difference range of -10 MPa to 10 MPa, indicating a further reduction in transmission loss. A trend of lower transmission loss is observed when the average stress of the fiber core is -80 MPa compared to when the average stress of the fiber core is -40 MPa.

[0060] Figure 5 It is a table that summarizes the specifications of each of the manufactured and evaluated MCFs. Figure 5 The MCFs in this context are all bi-core optical fibers consisting of only two cores, a first core and a second core. Figure 5 For each of the MCFs in samples B1 to B8, the average potassium (K) concentration [ppm], average core diameter [μm], average cutoff wavelength (λcc) [nm], and average effective cross-sectional area (Aeff) [μm] of the two cores are shown. 2 The ratio of compressive stress cross-sectional area [%), and the transmission loss [dB / km] of the first and second fiber cores at a wavelength of 1550nm respectively. As mentioned above, compressive stress here refers to the case where the residual stress is negative, and tensile stress refers to the case where the residual stress is positive.

[0061] Here, the proportion of compressive stress cross-sectional area is the ratio of the area of ​​the region becoming compressive stress to the area of ​​the entire region in the cross-section orthogonal to the fiber axis, i.e., the proportion of compressive stress cross-sectional area in the fiber cross-sectional area. The parameters of the second core are values ​​within ±5% of the parameters of the first core. The proportion of compressive stress cross-sectional area is varied by controlling the tension during drawing (drawing tension), the linear speed (drawing speed), and the slow cooling after exiting the furnace. The residual stress of the MCF is not a calculated value, but a measured value obtained using an optical system with a microscope and interferometer. It should be noted that, based on the residual stress distribution of the MCF, the proportion of compressive stress cross-sectional area in the fiber cross-sectional area is calculated as follows: First, the residual stress distribution of the MCF is divided into grids with a side length of less than 1 μm. Then, the total area of ​​all grids is set as the fiber cross-sectional area Aall. Additionally, the total area of ​​grids with negative residual stress, i.e., grids becoming compressive stress, is set as the compressive stress cross-sectional area Arg. Arg / Aall is calculated based on All and Arg obtained in this way and set as the proportion of compressive stress cross-sectional area in the fiber cross-sectional area.

[0062] Figure 6 This is a graph showing the relationship between the proportion of compressive stress cross-sectional area in the optical fiber and transmission loss. Since the transmission loss of the first and second fiber cores exhibits roughly the same trend, the first fiber core is shown here as a representative value. Figure 6 As shown, transmission loss is particularly low in the range where the proportion of the compressive stress cross-sectional area in the fiber cross-sectional area is approximately 15% to 25%. A trend of increasing transmission loss is observed when the proportion of the compressive stress cross-sectional area in the fiber cross-sectional area is smaller or larger than this range. The rationale for this is believed to be as follows.

[0063] Figure 7 This is a cross-sectional view illustrating an example of stress distribution in the MCF. Figure 7 In the diagram, the regions experiencing compressive stress are indicated by double-dotted lines. Stress distribution 1 simulates a case where the proportion of compressive stress in the fiber cross-sectional area is less than 15%. In stress distribution 1, only the two fiber cores 2 and their vicinity experience compressive stress, while a region between the two fiber cores 2 experiences tensile stress. It is believed that the region between the fiber cores 2 experiencing tensile stress in stress distribution 1 is the cause of increased transmission loss.

[0064] Stress distribution 2 simulates a case where the proportion of compressive stress in the fiber cross-sectional area is approximately 15% to 25%. In stress distribution 2, the regions of compressive stress centered on each fiber core overlap between the two fiber cores, while there are no regions of tensile stress between the two fiber cores.

[0065] Stress distribution 3 simulates a case where the proportion of compressive stress in the fiber cross-section is greater than 25%. In stress distribution 3, although there are no regions of tensile stress between fiber cores 2, regions of compressive stress persist up to most of the second cladding 4. It is believed that in stress distribution 3, the area of ​​the compressive stress region is too large to impart sufficient compressive stress to the fiber core 2, thus increasing transmission loss.

[0066] The embodiments have been described above, but this disclosure is not necessarily limited to the above embodiments and variations, and various changes can be made without departing from its spirit.

[0067] For example, two adjacent fiber cores 2 in a plurality of fiber cores 2 may have different shapes from each other. Two adjacent fiber cores 2 may also have different core diameters from each other. Two adjacent fiber cores 2 may also have different refractive indices from each other.

[0068] Explanation of reference numerals in the attached figures

[0069] 1. Multi-core optical fiber

[0070] 2 Fiber Core

[0071] 3 First cladding layer

[0072] 4 Second cladding

[0073] Line segment L.

Claims

1. A multi-core optical fiber, comprising silica-based glass, wherein the multi-core optical fiber comprises: Multiple fiber cores, comprising one or more elements from the alkali metal group, wherein the alkali metal group includes alkali metal elements and alkaline earth metal elements; and The cladding, which encloses the fiber core and has a refractive index lower than that of the fiber core, has a maximum residual stress in a cross section orthogonal to the fiber axis, such that the difference between the maximum residual stress and the average residual stress of the plurality of fiber cores on the line segment connecting the centers of adjacent fiber cores is less than 30 MPa.

2. The multi-core optical fiber according to claim 1, wherein, The difference is greater than -10MPa and less than 10MPa.

3. A multi-core optical fiber, comprising silica-based glass, wherein the multi-core optical fiber comprises: Multiple fiber cores, comprising one or more elements from the alkali metal group, wherein the alkali metal group includes alkali metal elements and alkaline earth metal elements; and The cladding, which encloses the fiber core, has a refractive index lower than that of the fiber core, and in a cross section orthogonal to the fiber axis, the area of ​​the region of compressive stress is less than 40% of the total area.

4. The multi-core optical fiber according to claim 3, wherein, In the cross section, the area of ​​the region that becomes compressive stress is less than 30% of the total area.

5. The multi-core optical fiber according to claim 3 or 4, wherein, In the cross section, the area of ​​the region that becomes compressive stress is more than 10% of the total area.

6. The multi-core optical fiber according to any one of claims 1 to 5, wherein, The plurality of fiber cores each contain one or more elements selected from sodium, potassium, rubidium, cesium, and calcium as the alkali metal element group.

7. The multi-core optical fiber according to any one of claims 1 to 6, wherein, The average concentration of the alkali metal element group in the multiple fiber cores is above 5 ppm and below 100 ppm.

8. The multi-core optical fiber according to any one of claims 1 to 7, wherein, The cladding includes a common first cladding covering the outer peripheral surfaces of multiple fiber cores 2 and a common second cladding covering the outer peripheral surfaces of the first cladding. The refractive index of the second cladding layer is higher than that of the first cladding layer. The relative refractive index difference of the fiber core, based on the refractive index of the first cladding, is 0.25% or more and 0.50% or less. The relative refractive index difference of the second cladding layer, based on the refractive index of the first cladding layer, is greater than 0.05% and less than 0.25%.

9. The multi-core optical fiber according to any one of claims 1 to 8, wherein, The multi-core optical fiber is a dual-core optical fiber.

10. The multi-core optical fiber according to any one of claims 1 to 9, wherein, In a cross section orthogonal to the fiber axis, the length of the line segment connecting the centers of adjacent fiber cores among the plurality of fiber cores is more than 20 μm and less than 50 μm.

11. The multi-core optical fiber according to any one of claims 1 to 10, wherein, The average residual stress, which is the compressive stress of the plurality of fiber cores, is above -100 MPa and below -20 MPa.

12. The multi-core optical fiber according to claim 1, wherein, The difference is below 20 MPa.

13. The multi-core optical fiber according to any one of claims 3 to 5, wherein, In the cross section, the area of ​​the region that becomes compressive stress is more than 15% and less than 25% of the total area.

14. The multi-core optical fiber according to any one of claims 1 to 13, wherein, The average cutoff wavelength of the multiple fiber cores is above 1300nm and below 1530nm.

15. The multi-core optical fiber according to any one of claims 1 to 14, wherein, The average effective cross-sectional area of ​​the multiple fiber cores at a wavelength of 1550 nm is 75 μm. 2 Above and 160μm 2 the following.

Citation Information

Patent Citations

  • Multicore fiber and optical cable

    JP2017040878A

  • Method of manufacturing multicore fiber

    JP2017075061A

  • Coupled multi-core optical fiber

    JP2017161705A

  • Power transmission device

    JP2023040847A